The reconstruction of the nasal ala with interpolated flaps from the cheek and forehead: design and execution modifications to improve surgical outcomes. (1st September 2014) - Cook, J.L.
Summary: The nasal ala, critically important in the function and appearance of the central face, has significant reconstructive demands given the lack of suitable adjacent donor tissue that can be used to repair all but the smallest surgical defects in this area. Interpolated flaps from the forehead and cheek have long been ideal reconstructive alternatives for the repair of larger or more difficult alar wounds, and with the design and execution modifications described here, the dermatological surgeon can offer more appropriate restoration of this critically important aesthetic unit.